CONCERTO: readout and control electronics. (1st October 2022) - Bourrion, O.; Hoarau, C.; Bounmy, J.; Tourres, D.; Vescovi, C.; Bouly, J.-L.; Ponchant, N.; Beelen, A.; Calvo, M.; Catalano, A.; Goupy, J.; Lagache, G.; et al.
Abstract: The CONCERTO spectral-imaging instrument was installed at the Atacama Pathfinder EXperiment (APEX) 12-meter telescope in April 2021. It has been designed to look at radiation emitted by ionised carbon atoms, [CII], and use the "intensity Mapping" technique to set the first constraints on the power spectrum of dusty star-forming galaxies. The instrument features two arrays of 2152 pixels constituted of Lumped Element Kinetic Inductance Detectors (LEKID) operated at cryogenic temperatures, cold optics and a fast Fourier Transform Spectrometer (FTS). To readout and operate the instrument, a newly designed electronic system hosted in five microTCA crates and composed of twelve readout boards and two control boards was designed and commissioned. The architecture and the performances are presented in this paper.